Indicators of gendered control over agricultural resources - Rao, Smriti (Assumption College, 2016)
This was the 4th in a series of webinars developed by the CGIAR Gender and Agriculture Research Network. This webinar was based on a recently released working paper. It was presented by Smriti Rao who prepared the working paper and moderated by Cheryl Doss from the CGIAR Research Program on Policies, Institutions and Markets.